Masalah Batas Usia Calon Presiden dan Calon Wakil Presiden: Studi Open Legal Policy dalam Putusan MK No. 90 90/PUU-XXI/2023 - Hardianto, Hanif; Krida Sakti, Sri Wahyu; Meliza, Meliza (Jurnal Supremasi, 2024)
Judicial review of Article 169 letter (q) of Law No. 7/2017 on General Elections resulted in 2 different decisions, namely the decision was rejected and the decision was granted. Case Number 90/PUU-XXI/2023 is a decision that was granted by the Constitutional Court. As a result of the granting of the judicial review, it caused uproar in the community, as well as the Article A quo is part of an open legal policy. The purpose of this research is to find out the Constitutional Court Decision Number 90/PUU-XXI/2023 on the testing of articles that are open legal policy by comparing previous Constitutional Court decisions. The research method used is normative juridical research. The result of the research is that judicial review cases with laws that are open legal policies are not the domain of the Constitutional Court to decide to grant, because the open legal policy is the domain of the legislature and the executive. The Court has indeed independence in deciding cases, but the Court also has the independence not to do something about the case. The Constitutional Court as the guardian and interpretator of constitutions must be actually implemented by the Constitutional Court Judges not only as a designation but different implementation.